PENGEMBANGAN MEDIA PEMBELAJARAN AUDIO VISUAL ADOBE FLASH PADA PEMBELAJARAN CARA PERAWATAN ANTI-LOCK BRAKE SYSTEM (Jurnal Penelitian Pendidikan Indonesia, 2023)
Technology development in the world of education is beneficial, especially in improving the quality of learning. Existing developments require the world of education to adapt. The characteristics of students in the XXI century who are the digitally literate generation make teachers have to be able to understand them so that there is a need for learning media that adapts to the development of technology. Specifically, this research aims to: Develop Android-based Adobe Flash Learning Media; Knowing the qualifications of the learning media on the basic competence of the anti-lock brake system; and Knowing the increase in the learning outcomes of basic anti-lock brake system competence of class XII students through Android-based adobe flash learning media. Research on the development of learning media in the form of this media uses the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation). The data analysis used in this research consists of: Determining the eligibility of learning media; Determine media effectiveness. Test media eligibility with the highly qualified category. The developed media was also tested for its effectiveness with an N-Gain value of 76%, which means that the developed media is effective. The calculated t value is 18.13 < t table then Ha is accepted while H0 is rejected, so it can be concluded that there is an influence of Android-based Adobe Flash audio-visual learning media on the basic competence of applying the Anti-Lock Brake System maintenance method for class XII TKRO 1 to improve student learning outcomes. Based on the results of the research, it can be concluded that the media that is developed is very suitable for improving the learning outcomes of basic anti-lock brake system competence in SMK students of light vehicle technical competence.